Peningkatan Hasil Belajar Siswa Menggunakan Pendekatan Konstruktivistik pada Pembelajaran IPS Kelas V SD Negeri 27 Siguhung Lubuk Basung - Taufik, Muhammad Ilham; Muhammadi, Muhammadi; Nasrul, Nasrul (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2015)
This research originated from the fact in elementary school (SD) that in the delivery of learning students are still less motivated to take lessons, so that the impact on student learning outcomes is low. The general purpose of the study is to describe an increase in student learning outcomes in social studies learning using a constructivist approach in Class V of SD Negeri 27 Siguhung Lubuk Basung. This study uses a qualitative and quantitative approach. The type of this research is Classroom Action Research (CAR) which carried out 2 cycles which included four stages, namely planning, implementation, observation and reflection. The subjects of this study were 22 fifth grade students of SD Negeri 27 Siguhung Lubuk Basung. The results showed an increase in: (a) RPP cycle I 85.71% (good) and cycle II 92.85% (very good) (b) Teacher activity cycle I 87.57% (good) and cycle II 95% (very good) . while the activities of the first cycle students 82.5% (good) and the second cycle 95% (very good) (c) Student learning outcomes in the first cycle 80.83 with a graduation percentage 81.82% increased in the second cycle to 86.65 with completeness percentage 95.45%. So it can be concluded that social studies learning using a constructivist approach can improve student learning outcomes. Keywords: Constructivistic Model, Learning Outcomes, IPS